2000
DOI: 10.1016/s1074-5521(00)00034-x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenicity of recombinant human pro-islet amyloid polypeptide (ProIAPP)

Abstract: Our studies suggest that ProIAPP has typical properties of an amyloidogenic polypeptide but also indicate that the pro-region suppresses the amyloidogenic and cytotoxic potentials of IAPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
42
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 74 publications
8
42
0
Order By: Relevance
“…An increase in production of proIAPP-like molecules could affect IAPP aggregation by several mechanisms. Firstly, proIAPP has been shown to form amyloid-like fibrils in vitro although with less avidity than IAPP [77]. Secondly, it has been shown that a synthetic construct of proIAPP with the N-terminal cleavage fragment intact, readily binds to heparan sulphate but IAPP does not [78].…”
Section: Aberrant Prohormone Processingmentioning
confidence: 99%
“…An increase in production of proIAPP-like molecules could affect IAPP aggregation by several mechanisms. Firstly, proIAPP has been shown to form amyloid-like fibrils in vitro although with less avidity than IAPP [77]. Secondly, it has been shown that a synthetic construct of proIAPP with the N-terminal cleavage fragment intact, readily binds to heparan sulphate but IAPP does not [78].…”
Section: Aberrant Prohormone Processingmentioning
confidence: 99%
“…Although not understood on a mechanistic level, impairment of prohormone processing has been thought to play a role in initiation and progression of T2D (22,23). Insulin and pro-IAPP (22,(24)(25)(26), but not proinsulin, can inhibit IAPP amyloid formation in vitro and in mice, suggesting that accumulation of unprocessed proinsulin may promote IAPP amyloid formation (22,24). Insulin-degrading enzyme (IDE) is a conserved metallopeptidase that can degrade insulin and a variety of other small peptides including IAPP in the pancreas (27,28).…”
mentioning
confidence: 99%
“…It is known that synthetic proIAPP can aggregate and form amyloid-like fibrils (30). Therefore, increased concentrations of proIAPP or IAPP intermediates could theoretically predispose to intracellular amyloid formation and thus represent the initial site for amyloid deposition.…”
mentioning
confidence: 99%